Kajian pembuatan mie basah tinggi serat dengan substitusi tepung porang dan pewarna alami [Study of making high fibre-wet noodles with porang flour substitution and natural dyes] - Dian Hasni; Cut Nilda; Jihan Riska Amalia (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
Wet noodles are a type of noodles that have undergone a boiling process with a water content of cooked wet noodles reaching 52%. Porang flour substituted wet noodles contain glucomannan which is a strong hydrocolloid and low in calories. This research has objectives to determine the best combination formulation of the porang flour substitution and types of natural dyes extract on physicochemical quality and consumer acceptance of this wet noodle. The factorial experiment was arranged in a randomized block design (RBD) with 2 factors using 3 replications. Factor A was porang flour substitution with 4 levels (A0 = control, A1 = 10%, A2 = 20%, A3 = 30%. Factor B was type of natural dye extract with 2 levels (B1 = carrot extract and B2 = beetroot extract). The measured parameters were noodle yield, breaking power, crude fibers, protein, moisture, and sensory quality using hedonic tests (aroma, taste, texture, and color). Wet noodles have the average yield value 168,40%, noodle breaking power 19,79%, moisture content 54,97%, protein content 9,41%, crude fiber 1,29%. For consumer acceptance, panelists tend to give neutral acceptance toward the aroma, color, taste and texture of the wet noodles. The best formulation was found in natural dyes of beetroot extract with 20% porang flour substitution (A2B2) which produces wet noodles according to SNI with the best physicochemical quality and sensory.Keywords: beet-root, glucomannan, natural dyes, porang flour, wet noodles